2017
DOI: 10.1103/physrevb.95.094517
|View full text |Cite
|
Sign up to set email alerts
|

Thermal expansion of the heavy-fermion superconductor PuCoGa5

Abstract: We have performed high-resolution powder x-ray diffraction measurements on a sample of 242 PuCoGa5, the heavy-fermion superconductor with the highest critical temperature Tc = 18.7 K. The results show that the tetragonal symmetry of its crystallographic lattice is preserved down to 2 K. Marginal evidence is obtained for an anomalous behaviour below Tc of the a and c lattice parameters. The observed thermal expansion is isotropic down to 150 K, and becomes anisotropic for lower temperatures. This gives a c/a ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…As an example of a high resolution XRD study, we show in Fig. 8 the results obtained for the PuCoGa 5 unconventional superconductor (Eloirdi et al, 2017). The experiment was performed at the ESRF ID22 beamline, affording a resolution ∆d/d = 10 −6 at λ = 0.354155 Å.…”
Section: B High Intensity and Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example of a high resolution XRD study, we show in Fig. 8 the results obtained for the PuCoGa 5 unconventional superconductor (Eloirdi et al, 2017). The experiment was performed at the ESRF ID22 beamline, affording a resolution ∆d/d = 10 −6 at λ = 0.354155 Å.…”
Section: B High Intensity and Resolutionmentioning
confidence: 99%
“…The shrinking of the cell volume is similar to the one observed for the CeRu 2 Si 2 Kondo system (Hiranaka et al, 2013) and could suggest the occurrence of critical valence Error bars have been estimated as 5× the statistical error provided by the Rietveld refinement and are smaller than the data symbol size. Adapted from (Eloirdi et al, 2017).…”
Section: B High Intensity and Resolutionmentioning
confidence: 99%
“…On the other hand, the relaxation rate isotope ratio T −1 1 ( 71 Ga)/T −1 1 ( 69 Ga) provided by Nuclear Quadrupole Resonance is not compatible with the presence of charge fluctuations in the normal state, but rather indicates the presence of anisotropic SFs [15] that could, nevertheless, be associated with charge (valence) fluctuations with a higher energy scale. High-resolution powder x-ray-diffraction recently showed that the volume expansion of PuCoGa 5 deviates from the curve expected for a simple Grüneisen-Einstein model, but the observed variations are too small to be taken as an indication for the proximity of the system to a valence instability [16]. The origin of SC in PuCoGa 5 remains therefore unclear.…”
mentioning
confidence: 97%
“…As an example of high resolution XRD study, we show in Fig. 3 the results obtained for the PuCoGa 5 unconventional superconductor (Eloirdi et al, 2017). The experiment was performed at the ESRF ID22 beamline, affording a resolution Ád/d = 10 À6 at = 0.354155 A ˚.…”
Section: Figurementioning
confidence: 99%